Slang: the communication of adolescents users of psychoactive substances - Zaléia Prado Brum; Débora Schlotefeldt Siniak (Universidade Federal de Santa Maria, 2011)
This study aimed to understand the communication used by adolescents, psychoactive substance users (PAS) by decoding the type of language adopted by them. Qualitative, descriptive research, conducted with young male living in a therapeutic community in the interior of the RS, in february 2010. Data were collected through Focus Group. The results came through content analysis, resulting in the thematic categories: name of person, expression of feeling, terms to objects and situations, codenames to drugs code. The data indicate that the slang used by teenagers is an important resource, especially to express feelings such as irony, contempt, humor, criticism, among others. It is concluded that this study brought a better understanding of communication used among teens in their daily lives and how this contributes to the nursing care and health promotion